(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Oligohydramnios are thought to be associated with increased maternal and fetal morbidities. Objective: To assess the obstetric and perinatal outcomes in case of isolated oligohydramnios. Materials and Methods: This study was conducted in the Obstetrics and Gynaecology department in Dhaka National Medical College Hospital from 1st July’ 2015 to 31st December 2015. Pregnant women at or beyond 34 weeks of gestation admitted for labour and delivery with low amniotic fluid index (AFI) ≤ 5cm, having no risk factors (group I) were compared with those with an AFI more than 5 cm (Group II). The mode of delivery and perinatal outcomes were compared to women having normal amniotic fluids. Results: A total 435 pregnant women were included in this study. Among them 67 pregnant women were in Group I and 368 women were in Group II. There were no demographic characteristics differences between the two groups. But there was significant difference in the gestational age of the mother. In group I 46% women delivered at 34-36 weeks of pregnancy. Regarding mode of delivery.caesarean section rate was more (P<.01) in group I than group II. There was no significant difference in meconium staining of liquor between the two groups. Regarding perinatal outcomes there were no significant differences between the two groups such as Apgar score, resuscitation, NICU admission and mortality of babies. But there was significant difference in the birth weight of the babies. About 66% of the babies in group I had birth weight < 2.5 kg, which was significant. Conclusion: Isolated oligohydramnios has no major effect on perinatal outcomes except low birth weight babies. However, caesarean section rate was increased in isolated oligohydramnios group. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 33-36